1986
DOI: 10.1200/jco.1986.4.11.1658
|View full text |Cite
|
Sign up to set email alerts
|

Soft-tissue and bone sarcoma histopathology peer review: the frequency of disagreement in diagnosis and the need for second pathology opinions. The Southeastern Cancer Study Group experience.

Abstract: Histopathologic peer review of specimens from 216 consecutive patients with soft-tissue or bone sarcomas on Southeastern Cancer Study Group protocols was performed by a panel of three pathologists. Subtype of sarcoma, degree of confidence in diagnosis, and grade were compared with agreement or disagreement in pathologic opinion from the primary member institution v the pathology review panel. The most common soft-tissue sarcoma was leiomyosarcoma, followed by malignant fibrous histiocytoma, fibrosarcoma, lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(68 citation statements)
references
References 2 publications
4
63
0
1
Order By: Relevance
“…Nevertheless it is surprising that, in spite of seeing relatively large numbers of sarcomas over and above normal workload, such variation in diagnosis between panel members continued to occur and although no formal assessment of converging agreement with time was made, the general impression was that this did not take place. This impression is consistent with that of Presant et al (1986) who found no improvement in frequency of agreement in the course of the SEG study, in spite of educational workshops. The only conclusion which can be drawn from this is that second opinion is of vital importance in cases of presumed sarcomas, particularly for those cases e.g.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Nevertheless it is surprising that, in spite of seeing relatively large numbers of sarcomas over and above normal workload, such variation in diagnosis between panel members continued to occur and although no formal assessment of converging agreement with time was made, the general impression was that this did not take place. This impression is consistent with that of Presant et al (1986) who found no improvement in frequency of agreement in the course of the SEG study, in spite of educational workshops. The only conclusion which can be drawn from this is that second opinion is of vital importance in cases of presumed sarcomas, particularly for those cases e.g.…”
Section: Resultssupporting
confidence: 80%
“…Presant et al (1986) reported the review of specimens from 216 consecutive patients with bone or soft tissue sarcomas entered into trials conducted by the Southeastern Cancer Study Group (SEG). Most cases were reviewed by one or two pathologists in addition to the original reviewer, and there was agreement between primary reviewer and panel in 66% cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Added to this is the observation that histopathological review often results in change in diagnosis of sub-type and may even result in certain tumours being redesignated as non-sarcomas (Presant et al, 1986;Alvegard & Berg, 1989, El-Jabbour et al, 1990Agnarsson et al, 1991).…”
mentioning
confidence: 99%